Poverty and Economic Justice in Pope Francis - Ilo, Stan Chu (2019)
This article discusses Pope Francis's teaching on poverty and economic justice with reference to his Evangelii gaudium and Laudato si'. This teaching is developed through three emphases of the pope: (1) a compassionate church, moved by the suffering and injustice in the world; (2) a church whose mission is to accompany humanity with the leaven of the Gospel in order to bring about a radical conversion of hearts and worldly systems and institutions; and (3) a transformative missional praxis that brings about integral salvation through solidarity with the poor and marginalized, and a prophetic commitment to human and cosmic flourishing.
Keywords: Africa; Catholic Social Teaching; God's kingdom; Pope Francis; Social Justice; Mission; Poverty